Gut-Lung Crosstalk in Sepsis-Induced Acute Lung Injury - Zhou, Xin; Liao, Youxia (Frontiers in Microbiology, 2021)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are common acute and severe cases of respiratory system with complicated pathogenesis and high mortality. Sepsis is the leading indirect cause of ALI/ARDS in intensive care unit (ICU). The pathogenesis of septic ALI/ARDS is complex and multifactorial. In the development of sepsis, the disruption of intestinal barrier function, the alteration of gut microbiota, and the translocation of intestinal microbiome can lead to systemic and local inflammatory responses, which further alter immune homeostasis in the systemic environment. Disruption of homeostasis may promote and propagate septic ALI/ARDS. In turn, when ALI occurs, elevated levels of inflammatory cytokines and the shift of the lung microbiome may lead to dysregulation of the intestinal microbiome and disruption of the intestinal mucosal barrier. Thus, the interaction between the lung and the gut can initiate and potentiate sepsis-induced ALI/ARDS. The gut–lung crosstalk may be a promising potential intervention target. This article reviews the underlying mechanism of gut-lung crosstalk in septic ALI/ARDS.